Farmer Empowerment in Improving Beef Cattle Farming Business in Tonsewer Village, Regency Minahasa - Lenzun, Gam D.; Lainawa, Jolyanis; Tumewu, Judy. M. (Journal of The Community Development in Asia, 2023)
The research objective was to examine the relationship between social engineering, economic engineering, technological engineering and value-added engineering with beef cattle business development in Tonsewer Village, West Tompaso District, Minahasa Regency based on farmers' perceptions. The analysis found that there is a significant relationship between the engineering variables and the variable of beef cattle business improvement. The level of relationship strength falls into the "strong relationship" category. Furthermore, this relationship is unidirectional, which means that if engineering increases, then beef cattle farming business will increase. Farmer empowerment strategies through; strengthening farmer institutions, counseling, and human resource development, access to capital, markets, achieving agreement on recommended technology with farmer habits, vertically and horizontally coordinated off farm business development.